Health, sovereignty and imperialism: The Royal Navy and infectious disease in Japan's treaty ports - Harrison, Mark (Social Science Diliman: A Philippine Journal of Society and Change; Vol 14 No 2 (2018), 2018)
During the 1860s and 1870s, the British Royal Navy was a major presence in Japanese treaty ports and influenced the development of public health in those cities in significant ways. This paper compares the Navy’s response to two of the major infectious disease issues in the treaty ports—cholera and venereal disease—with that of the Japanese. Its aim is to determine whether the presence of foreign powers that enjoyed significant extraterritorial rights served to stimulate or frustrate sanitary intervention. It is argued that while there was common ground between the approaches advocated and taken by the British and the Japanese in relation to venereal diseases, the British presence proved disruptive when it came to the control of cholera during the epidemic of 1877; an epidemic that appears to have originated on a British naval vessel. KEYWORDS: cholera, venereal disease, Royal Navy, Japan, treaty port, sovereignty